2017
DOI: 10.5195/jyd.2017.502
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Importance of Success and Failure Experiences at Summer Camp

Abstract: Young people can learn from success and failure. Such experiences are useful in developing skills (e.g., perseverance and coping), and remain essential facets of youth programming. However, success and failure can also impede development. Appraisal theory has been used widely to examine youths' experiences with success and failure in school and sport, yet summer camps represent an important setting where success and failure may look and feel different. In camp settings success or failure are often more subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Also, it was found that residential camps generate a stronger effect on the relationship between social capital and emotional intelligence than day camps. The effectiveness of summer camps and evaluation of students' success or failure have been investigated in a study conducted by Wilson and Sibthorp (2017) in which they stated that failure experiences are important to realize as such failures can result in unproductive and disrupt youths' engagement in positive youth development frameworks during summer camps.…”
Section: Dr Mohammadsoroush Tafazzolimentioning
confidence: 99%
“…Also, it was found that residential camps generate a stronger effect on the relationship between social capital and emotional intelligence than day camps. The effectiveness of summer camps and evaluation of students' success or failure have been investigated in a study conducted by Wilson and Sibthorp (2017) in which they stated that failure experiences are important to realize as such failures can result in unproductive and disrupt youths' engagement in positive youth development frameworks during summer camps.…”
Section: Dr Mohammadsoroush Tafazzolimentioning
confidence: 99%